First report of observation trial about impact of bisphosphonate`s treatment to the quality of life breast cancer patient with bone metastases - O. V. Zelenova; L. V. Bolotina; L. Yu. Nikitina; M. V. Chernikov (Опухоли женской репродуктивной системы, 2014)
Increasing survival of oncology patients depends on early diagnostics, developing the new technologies of the treatment and the new drugs. It allows finding out more and more patients with bone metastases. So the answers to the questions about bisphosphonate`s duration, complication of the treatment and improvement of quality of life are very necessary and important. We`ve analyzed long-term (1 year ) introduction of zoledronic acid 4 mg monthly in patients with breast cancer and bone metastasis. The data suggests that long-term treatment of zoledronic acid allows improving quality of life of this kind of patients.